ANALISIS KINERJA PERDAGANGAN SEKTOR ELEKTRONIK SEBELUM DAN SETELAH PELAKSANAAN CAFTA - Adrian D. Lubis (Buletin Ilmiah Litbang Perdagangan, 2010)
A lot of worries are emerging regarding to the negative impact of China ASEAN Free Trade Agreement (CAFTA) to domestic electronic industry. Yet, this kind of study using Trade Specialization Index, Bilateral Revealed Comparative Advantage and GTAP found that the trade deficit has occurred long before the implementation of CAFTA.Therefore, in order to encourage domestic electronic industry to improving its ability to take advantage of CAFTA implementation, government and private sector has to find win-win solution for producing some policies. These policies include cost production reducing, human source productivity increasing through some useful training and new technology application in producing high value added electronic products.